PERBEDAAN PROTOKOL PEMERIKSAAN KESEIMBANGAN STATIS DENGAN ONE LEG STANDING PADA LANSIA (Lembaga Penerbitan Universitas Esa Unggul, 2021)
Background: One of the most popular measurements in static balance tests in elderly population is one leg standing test. However, the one leg standing procedure varies in opened and closed eyes. Objective: This study was to investigated the procedure differences on the measurement of static balance with one leg standing in elderly population. Method: The experimental study was conducted on 34 elderly with MMSE value> 24 points. Do one leg standing with two sessions, 1st session standing on one leg with opened eyes, while 2nd session one leg standing with closed eyes. Each session is carried out 3 times with a 1 minute break between sessions. Results: Mann Whitney test with a sig value> (0.05) obtained results p-value 0.000 (p < 0.05). Conclusion: The results of this study was indicated that there is a significant difference in the value of one leg standing with opened eyes and one leg standing with closed eyes. Suggestion: The examination procedure will give different results. So it is recommended that clinician use the same procedure in evaluating patients with static balance problems.